Laminated body for transparent conductive film, transparent conductive film, and method for producing transparent conductive film
By using a cured resin layer composed of polymer components and curable monomers, the peeling and processing problems of the polyimide resin layer in the case of a thin layer are solved, and high heat resistance and good performance of the thin transparent conductive film are achieved.
Patent Information
- Application Number
- CN202180024883.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-03-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-03-26
AI Technical Summary
In the prior art, when forming a polyimide resin layer, especially in a thin layer, it is difficult to peel and process well, resulting in insufficient thickness of the transparent conductive film and insufficient heat resistance.
The cured resin layer consisting of polymer component (A) and curable monomer (B) was used, and the thermal deformation rate of heating to 150°C was controlled to be less than 1.2%, and the thickness was controlled to be less than 20 μm, and the process film was not installed. A cured resin layer is formed on the surface of the release layer to ensure its heat resistance and easy peelability.
The formation of a transparent conductive film with thin and excellent heat resistance is achieved, and deformation of the cured resin layer caused by heating is avoided, and the performance and operability of the transparent conductive layer are improved.
Smart Images

Figure CN115335224B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate for a transparent conductive film for forming a transparent conductive layer, a transparent conductive film using the laminate for a transparent conductive film, and a method for producing a transparent conductive film. Background Art
[0002] Transparent conductive films having a transparent conductive layer formed on the surface of a base film are used in liquid crystal displays, EL (electroluminescent) displays, EC (electrochromic) displays, solar cells, electromagnetic shielding films for electromagnetic shielding, transparent touch panels and other film sensors.
[0003] In the manufacturing process of the transparent conductive film, in many cases, it is processed under severe conditions accompanied by heating, such as sputtering of the metal compound and subsequent annealing. Therefore, high heat resistance is required for the laminate that becomes the substrate for forming the transparent conductive layer. For this reason, it can be considered to solve this problem by using the following laminate, which includes a film formed using a high heat-resistant resin such as a polyimide resin (for example, a resin with a glass transition temperature of 250°C or more).
[0004] In recent years, there has been a demand for reducing the thickness of a film of a high heat-resistant resin for the purpose of improving transparency and flexibility, reducing weight, and the like.
[0005] For example, Conventional Document 1 discloses a polyimide resin that is soluble in a solvent and can provide a highly transparent film by a solution casting method.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2017 / 179367 Summary of the invention
[0009] Problems to be solved by the invention
[0010] As described in patent document 1, when a polyimide resin layer is formed on a glass plate by a solution casting method, the polyimide resin layer can be easily peeled off from the glass plate. However, when a polyimide resin layer is formed on a resin sheet or a resin film by a solution casting method, the formed polyimide resin layer cannot be peeled off well from the resin sheet or the resin film, or cannot be peeled off at all. This tendency is particularly evident when the thickness of the polyimide film formed by the solution casting method is thin. In addition, it is also difficult to process the polyimide film by a roll-to-roll method.
[0011] In view of the above problems, the present invention aims to provide a laminate for a transparent conductive film that can obtain a thin transparent conductive film with excellent heat resistance, which can easily peel off the process film and has good characteristics. In addition, another object of the present invention is to provide a transparent conductive film with good characteristics, which is thin and has excellent heat resistance, and a method for producing the same.
[0012] Solution to the problem
[0013] The inventors of the present invention have conducted intensive research to solve the above-mentioned problems and have found that the above-mentioned problems can be solved by using a transparent conductive film laminate for forming a transparent conductive film, which has a process film and a cured resin layer in sequence and has the cured resin layer having a given thermal deformation rate and thickness, thereby completing the present invention.
[0014] That is, the present invention provides the following [1] to [9].
[0015] [1] A laminate for a transparent conductive film, which is a laminate for a transparent conductive film for forming a transparent conductive film, wherein:
[0016] The transparent conductive film laminate comprises a process film and a cured resin layer in this order.
[0017] The cured resin layer is a layer formed of a cured product of a curable resin composition, wherein the curable resin composition contains a polymer component (A) and a curable monomer (B).
[0018] The absolute value of the thermal deformation rate of the cured resin layer caused by heating to 150° C. is 1.2% or less,
[0019] The thickness of the cured resin layer is 20 μm or less.
[0020] The process film has a first surface optionally provided with a release layer and a second surface not provided with a release layer,
[0021] The cured resin layer is formed on the second surface of the process film.
[0022] [2] The laminate for a transparent conductive film according to [1] above, wherein
[0023] The glass transition temperature of the polymer component (A) is 250° C. or higher.
[0024] [3] The laminate for a transparent conductive film according to [1] or [2], wherein
[0025] The weight average molecular weight of the polymer component (A) is 100,000 or more.
[0026] [4] The laminate for a transparent conductive film according to any one of [1] to [3] above, wherein
[0027] The polymer component (A) is a polyimide resin.
[0028] [5] The laminate for a transparent conductive film according to [4] above, wherein
[0029] The above-mentioned polyimide resin is soluble in methyl ethyl ketone.
[0030] [6] The multilayer body for a transparent conductive film according to [4] or [5] above, wherein
[0031] The polyimide resin has a fluorine group in the molecule.
[0032] [7] The laminate for a transparent conductive film according to any one of [1] to [6], wherein
[0033] The cured resin layer has an elongation at break of 2.5% or more.
[0034] [8] A transparent conductive film having:
[0035] The laminate for a transparent conductive film as described in any one of the above [1] to [7], and
[0036] A transparent conductive layer is provided on the cured resin layer of the laminate for a transparent conductive film.
[0037] [9] A method for manufacturing a transparent conductive film, the method comprising:
[0038] a step of forming a conductive material layer on the cured resin layer of the laminate for a transparent conductive film according to any one of [1] to [7] above, and
[0039] The conductive material layer is heated to 140° C. or higher to form a transparent conductive layer.
[0040] Effects of the Invention
[0041] According to the present invention, a laminate for transparent conductive film can be provided, which can obtain a thin transparent conductive film with excellent heat resistance, which can easily peel off the process film, and has good characteristics. In addition, the present invention can provide a transparent conductive film with good characteristics, which is thin and has excellent heat resistance, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a cross-sectional schematic diagram showing a configuration example of the laminate for a transparent conductive film according to an embodiment of the present invention.
[0043] Figure 2It is a schematic cross-sectional view showing a configuration example of a transparent conductive film according to an embodiment of the present invention.
[0044] Figure 3 This is a process diagram showing an example of a method for producing a laminate for a transparent conductive film.
[0045] Figure 4 This is a process diagram showing an example of a method for producing a transparent conductive film.
[0046] Explanation of symbols
[0047] 1. 1A, 1B: Process film
[0048] 2: Curing resin layer
[0049] 2a: Curable resin layer (curable resin layer before curing)
[0050] 3: Transparent conductive layer
[0051] 3a: Conductive material layer
[0052] 10A, 10B: Laminated body for transparent conductive film
[0053] 20: Transparent conductive film
[0054] 21: Transparent conductive film after patterning of the transparent conductive layer
[0055] 31: Transparent conductive layer after patterning DETAILED DESCRIPTION
[0056] In this specification, the description "XX to YY" means "XX or more and YY or less".
[0057] In this specification, for example, "(meth)acrylic acid" means both "acrylic acid" and "methacrylic acid", and the same applies to other similar terms.
[0058] Hereinafter, a laminate for a transparent conductive film according to an embodiment of the present invention will be described.
[0059] 1. Laminated body for transparent conductive film
[0060] The transparent conductive film laminate according to the embodiment of the present invention comprises a process film and a cured resin layer in sequence. The cured resin layer is a layer formed by a cured product of a curable resin composition containing a polymer component (A) and a curable monomer (B), and the absolute value of the thermal deformation rate caused by heating to 150°C is less than 1.2%, and the thickness is less than 20 μm. In addition, the process film has a first surface, and a peeling layer may or may not be provided on the first surface. The cured resin layer is formed on the second surface of the process film on the opposite side of the surface having the peeling layer, and no peeling layer is provided on the second surface.
[0061] After intensive research, the inventors of the present invention have found the following. By (i) obtaining a cured resin layer from a curable resin composition containing a polymer component (A) and a curable monomer (B), and (ii) forming a cured resin layer on the surface of a process film that does not have a peeling layer, the curable resin composition can be well coated on the process film to form a cured resin layer well. In addition, even if the cured resin layer is formed to a thickness of 10 μm or less, the cured resin layer can be easily peeled off from the process film. In addition, by (iii) setting the thermal deformation rate of the cured resin layer caused by heating to 150° C. to less than 1.2%, the cured resin layer can withstand the heat load when a transparent conductive layer is formed on the cured resin layer, thereby preventing deformation of the cured resin layer. As a result, the performance degradation of the transparent conductive layer is suppressed, and a transparent conductive film with good characteristics can be obtained.
[0062] Hereinafter, for easy understanding, the configuration of each layer and film will be described with reference to the drawings as appropriate and using the reference numerals shown in the drawings, but the present invention is not limited to the embodiments shown in the drawings.
[0063] The specific configuration of the laminate for a transparent conductive film according to an embodiment of the present invention is shown in Figure 1 .
[0064] Figure 1 The laminated body 10A for transparent conductive film shown in (a) has a process film 1 on one side of a cured resin layer 2. As described later, a transparent conductive layer is provided on the side of the cured resin layer 2 opposite to the process film 1 to form a transparent conductive film.
[0065] Figure 1 The transparent conductive film laminate 10B shown in (b) has process films 1A and 1B on both sides of the cured resin layer 2. When a transparent conductive layer is to be provided, either of the process films 1A and 1B is peeled off and removed, and then a transparent conductive layer is provided on the exposed surface.
[0066] In this case, at least one of the process films 1A and 1B is laminated on the cured resin layer in a state where the second surface faces the cured resin layer.
[0067] 1-1. Curing resin layer
[0068] The cured resin layer of the laminate for transparent conductive film according to the embodiment of the present invention is formed of a cured product of a curable resin composition containing a polymer component (A) and a curable monomer (B). The cured resin layer may be a single layer or may include a plurality of stacked layers.
[0069] [Polymer component (A)]
[0070] The glass transition temperature (Tg) of the polymer component (A) is preferably 250° C. or higher, more preferably 290° C. or higher, and further preferably 320° C. or higher. When the Tg of the polymer component (A) is 250° C. or higher, it is easy to impart sufficient heat resistance to the cured resin layer, and when forming the transparent conductive layer, it is easy to prevent the cured resin layer from being affected by heating such as annealing treatment and deforming.
[0071] Furthermore, by setting the Tg of the polymer component (A) to 250°C or higher and preparing a curable composition together with the curable monomer (B) described below, it is easy to avoid a decrease in heat resistance by the influence of the polymer generated when the curable composition is cured.
[0072] Here, Tg refers to the temperature at which tan δ (loss modulus / storage modulus) obtained by viscoelasticity measurement (measurement in a tensile mode in the range of 0 to 250° C. under the conditions of a frequency of 11 Hz and a heating rate of 3° C. / min) is the maximum point.
[0073] The weight average molecular weight (Mw) of the polymer component (A) is preferably 100,000 or more, more preferably 200,000 or more, and is preferably 1,000,000 or less, more preferably 800,000 or less, and even more preferably 500,000 or less.
[0074] In addition, the molecular weight distribution (Mw / Mn) of the polymer component (A) is preferably in the range of 1.0 to 5.0, more preferably in the range of 2.0 to 4.5. The weight average molecular weight (Mw) and the molecular weight distribution (Mw / Mn) are polystyrene-converted values measured by gel permeation chromatography (GPC). By setting Mw to 100,000 or more, it is easy to increase the elongation at break of the cured resin layer.
[0075] As the polymer component (A), a thermoplastic resin is preferred, and an amorphous thermoplastic resin is more preferred. By using an amorphous thermoplastic resin, it is easy to obtain a cured resin layer with excellent optical isotropy, and it is easy to obtain a laminate for a transparent conductive film with excellent transparency. In addition, an amorphous thermoplastic resin is generally easily soluble in an organic solvent, and therefore, as described later, a cured resin layer can be efficiently formed by a solution casting method.
[0076] Here, the amorphous thermoplastic resin refers to a thermoplastic resin whose melting point is not observed in differential scanning calorimetry.
[0077] The polymer component (A) is particularly preferably soluble in a low-boiling general-purpose organic solvent such as ethyl acetate and methyl ethyl ketone (MEK). When the polymer component (A) is soluble in a general-purpose organic solvent, it is easy to form a cured resin layer by coating.
[0078] As the polymer component (A), an amorphous thermoplastic resin which is soluble in a low-boiling-point general-purpose organic solvent such as ethyl acetate and methyl ethyl ketone and has a Tg of 250° C. or higher is particularly preferred.
[0079] In addition, as the polymer component (A), from the viewpoint of heat resistance, a thermoplastic resin having a ring structure such as an aromatic ring structure or an alicyclic structure is preferred, and a thermoplastic resin having an aromatic ring structure is more preferred.
[0080] Specific examples of the polymer component (A) include polyimide resins and polyarylate resins having a Tg of 250° C. or higher. These resins generally have a high Tg and excellent heat resistance, and since they are amorphous thermoplastic resins, they can be formed into a coating film by a solution casting method. Among them, polyimide resins are preferred from the viewpoint of having a high Tg, excellent heat resistance, and being easy to obtain a component that exhibits good heat resistance and is soluble in a general organic solvent.
[0081] The polyimide resin is not particularly limited as long as it does not impair the effects of the present invention, and for example, aromatic polyimide resins, aromatic (carboxylic acid component)-cycloaliphatic (diamine component) polyimide resins, cycloaliphatic (carboxylic acid component)-aromatic (diamine component) polyimide resins, cycloaliphatic polyimide resins, and fluorinated aromatic polyimide resins can be used. Polyimide resins having a fluorine group in the molecule are particularly preferred.
[0082] Specifically, a polyimide resin obtained by polymerization of an aromatic diamine compound and tetracarboxylic dianhydride to a polyamic acid and chemical imidization reaction is preferred.
[0083] As the aromatic diamine compound, any aromatic diamine compound can be used as long as it is a compound that can give a polyimide that is soluble in a common solvent (for example, N,N-dimethylacetamide (DMAC)) and has a predetermined transparency by reacting with tetracarboxylic dianhydride used in combination. Specific examples include m-phenylenediamine, p-phenylenediamine, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)propane, 2-(3-aminophenyl)-2-(4-aminophenyl)-propane, phenyl)propane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2-(3-aminophenyl)-2-(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 3,4'-bis(3-aminophenoxy) )biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenyl)]sulfone, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenyl)]sulfone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ether, bis[ 4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-fluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, etc.
[0084] These aromatic diamine compounds may be used alone or in combination of two or more aromatic diamine compounds. Among them, from the viewpoint of transparency and heat resistance, preferred aromatic diamine compounds include 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2-(3-aminophenyl)-2-(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(3-aminophenyl)-2-(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane The present invention can be used to prepare an aromatic diamine compound having a fluorine group, such as 1,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl. It is preferred that at least one of the aromatic diamine compounds used is an aromatic diamine compound having a fluorine group, and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl is particularly preferred. By using an aromatic diamine compound having a fluorine group, transparency, heat resistance, and solubility in a solvent are easily obtained.
[0085] As the tetracarboxylic dianhydride, similar to the above-mentioned aromatic diamine compound, any tetracarboxylic dianhydride can be used as long as it is soluble in a common solvent (for example, N,N-dimethylacetamide (DMAC)) and can give a polyimide having a given transparency, and specific examples thereof include: 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride, pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 1,4-hydroquinone dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ethertetracarboxylic dianhydride, etc. These tetracarboxylic dianhydrides may be used alone, or two or more tetracarboxylic dianhydrides may be used. Among them, from the viewpoint of transparency, heat resistance, and solubility in solvents, it is preferred to use at least one tetracarboxylic dianhydride having a fluorine group such as 4,4′-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride.
[0086] The polymerization to polyamic acid can be carried out by reacting the aromatic diamine compound and tetracarboxylic dianhydride under the condition of being dissolved in a solvent that can dissolve the polyamic acid to be produced. As the solvent used for the polymerization to polyamic acid, solvents such as N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, and dimethyl sulfoxide can be used.
[0087] The polymerization reaction to the polyamic acid is preferably carried out while stirring using a reaction vessel equipped with a stirring device. For example, there can be mentioned a method in which a given amount of an aromatic diamine compound is dissolved in the above-mentioned solvent, tetracarboxylic dianhydride is added while stirring, and the reaction is carried out to obtain a polyamic acid; a method in which tetracarboxylic dianhydride is dissolved in a solvent, an aromatic diamine compound is added while stirring, and the reaction is carried out to obtain a polyamic acid; a method in which an aromatic diamine compound and tetracarboxylic dianhydride are alternately added, and the reaction is carried out to obtain a polyamic acid, etc.
[0088] The polymerization temperature to the polyamic acid is not particularly limited, but is preferably 0 to 70° C., more preferably 10 to 60° C., and further preferably 20 to 50° C. By performing the polymerization reaction within the above range, a high molecular weight polyamic acid with little coloration and excellent transparency can be obtained.
[0089] In addition, the aromatic diamine compound and tetracarboxylic dianhydride used for the polymerization of polyamic acid are basically used in equimolar amounts, but in order to control the degree of polymerization of the obtained polyamic acid, the molar amount of tetracarboxylic dianhydride / molar amount of aromatic diamine compound (molar ratio) can also be changed in the range of 0.95 to 1.05. Among them, the molar ratio of tetracarboxylic dianhydride to aromatic diamine compound is preferably in the range of 1.001 to 1.02, and more preferably 1.001 to 1.01. In this way, by making tetracarboxylic dianhydride slightly excessive relative to the aromatic diamine compound, the degree of polymerization of the obtained polyamic acid can be stabilized, and the unit derived from tetracarboxylic dianhydride can be configured at the end of the polymer, as a result, a polyimide with less coloring and excellent transparency can be obtained.
[0090] The concentration of the generated polyamic acid solution is preferably adjusted to an appropriate concentration (for example, about 10 to 30% by mass) that can maintain a suitable solution viscosity and facilitate handling in the subsequent steps.
[0091] An imidization agent is added to the obtained polyamic acid solution to carry out chemical imidization. As an imidization agent, carboxylic anhydrides such as acetic anhydride, propionic anhydride, succinic anhydride, phthalic anhydride, and benzoic anhydride can be used. From the perspective of cost and ease of removal after the reaction, acetic anhydride is preferably used. The equivalent of the imidization agent used is more than the equivalent of the amide bond of the polyamic acid to be chemically imidized, preferably 1.1 to 5 times the equivalent of the amide bond, and more preferably 1.5 to 4 times. By using an imidization agent in a small amount in excess relative to the amide bond like this, imidization can also be effectively carried out at a relatively low temperature.
[0092] In the chemical imidization reaction, aliphatic, aromatic or heterocyclic tertiary amines such as pyridine, picoline, quinoline, isoquinoline, trimethylamine, triethylamine, etc. can be used as imidization accelerators. By using such amines, the imidization reaction can be effectively carried out at low temperatures, and as a result, the coloring during the imidization reaction can be suppressed, and a more transparent polyimide can be easily obtained.
[0093] The chemical imidization reaction temperature is not particularly limited, but is preferably 10° C. to less than 50° C., more preferably 15° C. to less than 45° C. By carrying out the chemical imidization reaction at a temperature of 10° C. to less than 50° C., coloration during the imidization reaction can be suppressed, and a polyimide having excellent transparency can be obtained.
[0094] Thereafter, the polyimide solution obtained by chemical imidization reaction is subjected to powderization and drying as required. The powderization is performed by adding a poor solvent for polyimide to precipitate the polyimide to form a powder.
[0095] The polyimide resin is preferably soluble in a low-boiling point organic solvent such as ethyl acetate and methyl ethyl ketone. It is particularly preferably soluble in methyl ethyl ketone. When soluble in methyl ethyl ketone, a layer of a curable resin composition can be easily formed by coating and drying.
[0096] A polyimide resin containing a fluorine group is particularly preferred because it is easily soluble in a general-purpose organic solvent having a low boiling point, such as methyl ethyl ketone, and a cured resin layer can be easily formed by a coating method.
[0097] As the polyimide resin having a fluorine group, an aromatic polyimide resin having a fluorine group in the molecule is preferred, and a polyimide resin having a skeleton represented by the following chemical formula in the molecule is preferred.
[0098] [Chemical formula 1]
[0099]
[0100] The polyimide resin having the skeleton shown in the above chemical formula has an extremely high Tg of more than 300°C due to the high rigidity of the above skeleton. Therefore, the heat resistance of the cured resin layer can be greatly improved. In addition, the above skeleton is linear and has high flexibility, which makes it easy to improve the elongation at break of the cured resin layer. In addition, the polyimide resin having the above skeleton can be dissolved in a low-boiling general organic solvent such as methyl ethyl ketone by having a fluorine group. Therefore, a solution casting method can be used for coating to form a cured resin layer in the form of a coating film, and the solvent can also be easily removed by drying. The polyimide resin having the skeleton shown in the above chemical formula can be obtained by using 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl) diphthalic anhydride, through the polymerization and imidization reaction of the above polyamic acid.
[0101] Polyarylate resin is a resin formed by a polymer compound obtained by reacting an aromatic diol with an aromatic dicarboxylic acid or its acyl chloride. Polyarylate resin has a high Tg and good elongation properties. There is no particular limitation on the polyarylate resin, and known resins can be used.
[0102] Examples of the aromatic diol include bis(hydroxyphenyl)alkanes such as bis(4-hydroxyphenyl)methane [bisphenol F], bis(3-methyl-4-hydroxyphenyl)methane, 1,1-bis(4'-hydroxyphenyl)ethane, 1,1-bis(3'-methyl-4'-hydroxyphenyl)ethane, 2,2-bis(4'-hydroxyphenyl)propane [bisphenol A], 2,2-bis(3'-methyl-4'-hydroxyphenyl)propane, 2,2-bis(4'-hydroxyphenyl)butane, and 2,2-bis(4'-hydroxyphenyl)octane; and 1,1-bis(4'-hydroxyphenyl)cyclopentane, 1,1-bis(4'-hydroxyphenyl)cyclohexane [bisphenol Z], and 1,1-bis(4'-hydroxyphenyl)-3,3,5-trimethylcyclohexane. Bis(hydroxyphenyl)cycloalkanes; bis(4-hydroxyphenyl)phenylmethane, bis(3-methyl-4-hydroxyphenyl)phenylmethane, bis(2,6-dimethyl-4-hydroxyphenyl)phenylmethane, bis(2,3,6-trimethyl-4-hydroxyphenyl)phenylmethane, bis(3-tert-butyl-4-hydroxyphenyl)phenylmethane, bis(3-phenyl-4-hydroxyphenyl)phenylmethane, bis(3-fluoro-4-hydroxyphenyl)phenylmethane, bis(3-bromo-4-hydroxyphenyl)phenylmethane, bis(4-hydroxyphenyl)-4-fluorophenylmethane, bis(3-fluoro-4-hydroxyphenyl)-4-fluorophenylmethane, bis(4-hydroxyphenyl)-4-chlorophenylmethane, bis(4-hydroxyphenyl)-4-bromophenylmethane, bis(3,5-dihydroxyphenyl)phenylmethane 1,1-bis(4'-hydroxyphenyl)-1-phenylethane [bisphenol P], 1,1-bis(3'-methyl-4'-hydroxyphenyl)-1-phenylethane, 1,1-bis(3'-tert-butyl-4'-hydroxyphenyl)-1-phenylethane, 1,1-bis(3'-phenyl-4'-hydroxyphenyl)-1-phenylethane, 1,1-bis(4'-hydroxyphenyl)-1-(4'-nitrophenyl)ethane, 1,1-bis(3'-bromo-4'-hydroxyphenyl)-1-phenylethane, 1,1-bis(4'-hydroxyphenyl)-1-phenylpropane, bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl)bibenzylmethane, etc. Hydrocarbons; bis(hydroxyphenyl) ethers such as bis(4-hydroxyphenyl) ether and bis(3-methyl-4-hydroxyphenyl) ether; bis(hydroxyphenyl) ketones such as bis(4-hydroxyphenyl) ketone and bis(3-methyl-4-hydroxyphenyl) ketone; bis(hydroxyphenyl) sulfides such as bis(4-hydroxyphenyl) sulfide and bis(3-methyl-4-hydroxyphenyl) sulfide; bis(hydroxyphenyl) sulfoxides such as bis(4-hydroxyphenyl) sulfoxide and bis(3-methyl-4-hydroxyphenyl) sulfoxide; bis(hydroxyphenyl) sulfones such as bis(4-hydroxyphenyl) sulfone [bisphenol S] and bis(3-methyl-4-hydroxyphenyl) sulfone; bis(hydroxyphenyl) fluorenes such as 9,9-bis(4'-hydroxyphenyl) fluorene and 9,9-bis(3'-methyl-4'-hydroxyphenyl) fluorene; etc.
[0103] As aromatic dicarboxylic acids or their acid chlorides, for example, phthalic acid, isophthalic acid, terephthalic acid, 4,4'-biphenyl dicarboxylic acid, diphenoxyethane dicarboxylic acid, diphenyl ether 4,4'-dicarboxylic acid, 4,4'-diphenyl sulfone dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and their acid chlorides, etc. In addition, the polyarylate resin used may also be a modified polyarylate resin. Among them, as the polyarylate resin, a resin formed by a polymer compound obtained by reacting 2,2-bis(4'-hydroxyphenyl)propane with isophthalic acid is preferred.
[0104] The polymer component (A) can be used alone or in combination of two or more. In addition, as the polymer component (A), a polymer component (A') having a glass transition temperature of 250°C or more and a polymer component (A") having a glass transition temperature of less than 250°C can be used in combination. As the polymer component (A"), for example, polyamide resins and polyarylate resins having a Tg of less than 250°C can be cited, preferably polyamide resins.
[0105] The polyamide resin is preferably soluble in an organic solvent, and is preferably a rubber-modified polyamide resin. As the rubber-modified polyamide resin, for example, resins described in Japanese Unexamined Patent Publication No. 2004-035638 can be used.
[0106] From the viewpoint of being able to adjust the elongation characteristics and the viewpoint of solvent resistance, the polymer component (A) and the polymer component (A") are preferably a component using a single type of polyimide resin, a component using a plurality of different polyimide resins, and a component in which at least one of a polyamide resin and a polyarylate resin is added to a polyimide resin.
[0107] When a polyamide resin or a polyarylate resin having a Tg of less than 250° C. is added to a polyimide resin, the amount of the added resin is preferably 100 parts by mass or less, more preferably 70 parts by mass or less, further preferably 50 parts by mass or less, and further preferably 30 parts by mass or less, relative to 100 parts by mass of the polyimide resin, from the viewpoint of maintaining a high Tg and imparting moderate flexibility. In addition, it is preferably 1 part by mass or more, and more preferably 3 parts by mass or more.
[0108] [Curable Monomer (B)]
[0109] The curable monomer (B) is a monomer having a polymerizable unsaturated bond, and is a monomer for polymerization reaction or a monomer that can participate in polymerization reaction. By using the curable monomer (B), the peeling of the cured resin layer from the process film becomes easy. In addition, a laminate for transparent conductive film having excellent solvent resistance can be obtained.
[0110] By making the cured resin layer a layer formed of a cured product of a curable resin composition containing the above-mentioned polymer component (A) and the above-mentioned curable monomer (B), a cured resin layer having excellent heat resistance and being thin can be easily formed. In addition, when such a material is used, optical problems caused by materials having anisotropic molecular orientation, such as polyester films, which are generally used as substrates for transparent conductive film laminates, will not occur. In addition, by making the absolute value of the thermal deformation rate of the cured resin layer caused by heating to 150°C less than 1.2%, the cured resin layer shows heat resistance. Therefore, when the conductive material layer is heated to form a transparent conductive layer, the deformation of the cured resin layer caused by heating, etc., which causes the performance of the transparent conductive layer to be reduced, can be suppressed.
[0111] Furthermore, according to the research of the inventors, the resin layer formed by dissolving a polyimide resin in a solvent without using a curable monomer (B) and coating / drying it on a silicone resin release film as a common release film has a tendency to increase haze due to the influence of the unevenness existing on the surface of the release film. In contrast, by using a curable monomer (B) in combination, even if a cured resin layer is provided on the second surface of a process film without a release layer, the cured resin layer can be easily peeled off, thereby suppressing the increase in haze.
[0112] The molecular weight of the curable monomer (B) is usually 3000 or less, preferably 200 to 2000, and more preferably 200 to 1000. When the molecular weight of the curable monomer (B) is within such a range, skinning described below can be more effectively suppressed when forming a coating film of the curable resin composition.
[0113] The number of polymerizable unsaturated bonds in the curable monomer (B) is not particularly limited. The curable monomer (B) may be a monofunctional monomer having one polymerizable unsaturated bond, or a polyfunctional monomer such as a bifunctional monomer or a trifunctional monomer having a plurality of polymerizable unsaturated bonds.
[0114] Examples of the monofunctional monomer include monofunctional (meth)acrylic acid derivatives.
[0115] The monofunctional (meth)acrylic acid derivative is not particularly limited, and known compounds can be used, and examples thereof include monofunctional (meth)acrylic acid derivatives having a nitrogen atom, monofunctional (meth)acrylic acid derivatives having an alicyclic structure, and monofunctional (meth)acrylic acid derivatives having a polyether structure.
[0116] Examples of the monofunctional (meth)acrylic acid derivative having a nitrogen atom include compounds represented by the following formula.
[0117] [Chemical formula 2]
[0118]
[0119] In the formula, R 1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, R 2 and R 3 Each independently represents a hydrogen atom or an organic group having 1 to 12 carbon atoms, and R 2 and R 3 Can bond to form a ring structure, R 4 It represents a divalent organic group.
[0120] As R 1 Examples of the alkyl group having 1 to 6 carbon atoms include methyl group, ethyl group, propyl group and the like, and methyl group is preferred.
[0121] As R 2 and R 3 The organic group having 1 to 12 carbon atoms represented by may include: alkyl groups having 1 to 12 carbon atoms such as methyl, ethyl, and propyl; cycloalkyl groups having 3 to 12 carbon atoms such as cyclopentyl and cyclohexyl; and aromatic groups having 6 to 12 carbon atoms such as phenyl, biphenyl, and naphthyl. These groups may have a substituent at any position. 2 and R 3 They may form a ring together, and the ring may further have a nitrogen atom or an oxygen atom in the skeleton.
[0122] As R 4 The divalent organic group represented by m -、-NH-(CH2) m Here, m is an integer of 1 to 10.
[0123] Among them, as a preferred example of the monofunctional (meth)acrylic acid derivative having a nitrogen atom, (meth)acryloylmorpholine represented by the following formula can be mentioned.
[0124] [Chemical formula 3]
[0125]
[0126] By using a monofunctional (meth)acrylic acid derivative having a nitrogen atom as the curable monomer (B), a cured resin layer having more excellent heat resistance can be formed.
[0127] Examples of the monofunctional (meth)acrylic acid derivative having an alicyclic structure include compounds represented by the following formula.
[0128] [Chemical formula 4]
[0129]
[0130] In the formula, R 1 Means the same as above, R 5 It is a group having an alicyclic structure.
[0131] As R 5 Examples of the group having an alicyclic structure represented by include a cyclohexyl group, an isobornyl group, a 1-adamantyl group, a 2-adamantyl group, and a tricyclodecanyl group.
[0132] Specific examples of the monofunctional (meth)acrylic acid derivative having an alicyclic structure include isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, and the like.
[0133] By using a monofunctional (meth)acrylic acid derivative having an alicyclic structure as the curable monomer (B), a cured resin layer having more excellent optical properties can be formed.
[0134] Examples of the monofunctional (meth)acrylic acid derivative having a polyether structure include compounds represented by the following formula.
[0135] [Chemical formula 5]
[0136]
[0137] In the formula, R 1 Means the same as above, R 6 represents an organic group having 1 to 12 carbon atoms. 6 The organic group having 1 to 12 carbon atoms represented by j includes alkyl groups having 1 to 12 carbon atoms such as methyl, ethyl, and propyl; cycloalkyl groups having 3 to 12 carbon atoms such as cyclohexyl; aromatic groups having 6 to 12 carbon atoms such as phenyl, biphenyl, and naphthyl; etc. j represents an integer of 2 to 20.
[0138] Specific examples of the monofunctional (meth)acrylic acid derivative having a polyether structure include epoxidized o-phenylphenol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate.
[0139] By using a monofunctional (meth)acrylic acid derivative having a polyether structure as the curable monomer (B), a cured resin layer having excellent toughness can be formed.
[0140] Examples of the polyfunctional monomer include polyfunctional (meth)acrylic acid derivatives.
[0141] The polyfunctional (meth)acrylic acid derivative is not particularly limited, and a known compound can be used. For example, bi- to hexa-functional (meth)acrylic acid derivatives are mentioned.
[0142] Examples of the bifunctional (meth)acrylic acid derivative include compounds represented by the following formula.
[0143] [Chemical formula 6]
[0144]
[0145] In the formula, R 1 Means the same as above, R 7 represents a divalent organic group. 7 Examples of the divalent organic group represented by include groups represented by the following formulae.
[0146] [Chemical formula 7]
[0147] -O-(CH2) s -O-
[0148] -O(CH2CH2O) t -
[0149]
[0150] (In the formula, s represents an integer of 1 to 20, t represents an integer of 1 to 30, u and v each independently represent an integer of 1 to 30, and "-" at both ends represents a bonding site.)
[0151] Specific examples of the bifunctional (meth)acrylic acid derivatives represented by the above formula include tricyclodecane dimethanol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propoxylated ethoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, etc. Among them, from the viewpoint of heat resistance and toughness, tricyclodecane dimethanol di(meth)acrylate and the like are preferably used. 7 The divalent organic group represented by the compound has a tricyclodecane skeleton; propoxylated ethoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, etc. In the above formula, R 7 The divalent organic group represented by the compound has a bisphenol skeleton; 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, etc. In the above formula, R 7 The divalent organic group represented by is a compound having a 9,9-bisphenylfluorene skeleton.
[0152] In addition, examples of other bifunctional (meth)acrylic acid derivatives include neopentyl glycol adipate di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, di(acryloyloxyethyl)isocyanurate, and allyl cyclohexyl di(meth)acrylate.
[0153] Examples of the trifunctional (meth)acrylic acid derivative include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.
[0154] Examples of the tetrafunctional (meth)acrylic acid derivative include pentaerythritol tetra(meth)acrylate and the like.
[0155] Examples of the pentafunctional (meth)acrylic acid derivative include propionic acid-modified dipentaerythritol penta(meth)acrylate and the like.
[0156] Examples of the hexafunctional (meth)acrylic acid derivative include dipentaerythritol hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0157] As the curable monomer (B), a cyclopolymerizable monomer may also be used. As the cyclopolymerizable monomer, a monomer having the property of undergoing free radical polymerization while undergoing cyclization may be cited. As the cyclopolymerizable monomer, a non-conjugated diene may be cited, for example, an α-allyloxymethyl acrylic acid monomer may be used, preferably an alkyl ester of 2-allyloxymethyl acrylic acid having 1 to 4 carbon atoms, 2-(allyloxymethyl) cyclohexyl acrylate, more preferably an alkyl ester of 2-allyloxymethyl acrylic acid having 1 to 4 carbon atoms, and further preferably methyl 2-(allyloxymethyl) acrylate.
[0158] In addition, cyclopolymerizable monomers such as dimethyl 2,2'-[oxybis(methylene)]bis-2-acrylate, diethyl 2,2'-[oxybis(methylene)]bis-2-acrylate, di-n-propyl 2,2'-[oxybis(methylene)]bis-2-acrylate, diisopropyl 2,2'-[oxybis(methylene)]bis-2-acrylate, di-n-butyl 2,2'-[oxybis(methylene)]bis-2-acrylate, di-n-hexyl 2,2'-[oxybis(methylene)]bis-2-acrylate, and dicyclohexyl 2,2'-[oxybis(methylene)]bis-2-acrylate can also be used.
[0159] The curable monomer (B) may be used alone or in combination of two or more.
[0160] Among them, from the viewpoint of obtaining a cured resin layer with better heat resistance and solvent resistance, the curable monomer (B) is preferably a multifunctional monomer. As a multifunctional monomer, from the viewpoint of being easy to mix with the polymer component (A), not easily shrinking the polymer upon curing, and being able to suppress the curling of the cured product, a bifunctional (meth) acrylic acid derivative is preferred.
[0161] As the curable monomer (B), it is more preferable to contain a multifunctional (meth)acrylate compound and a cyclopolymerizable monomer. By using them in combination, it is easy to adjust the heat resistance of the cured resin layer to an appropriate level and the elongation at break of the cured resin layer to a given range.
[0162] When the curable monomer (B) contains a multifunctional monomer, the content thereof is preferably 40% by mass or more, more preferably 50 to 100% by mass, based on the total amount of the curable monomer (B).
[0163] [Curable resin composition]
[0164] The curable resin composition for forming the cured resin layer according to the embodiment of the present invention can be prepared by mixing the polymer component (A), the curable monomer (B), and the polymerization initiator and other components added as desired and dissolving or dispersing them in an appropriate solvent.
[0165] The total content of the polymer component (A) and the curable monomer (B) in the curable resin composition is preferably 40 to 99.5% by mass, more preferably 60 to 99% by mass, and even more preferably 80 to 98% by mass, based on the total mass of the curable resin composition excluding the solvent.
[0166] The content of the polymer component (A) and the curable monomer (B) in the curable resin composition is preferably polymer component (A):curable monomer (B) = 30:70 to 90:10, more preferably 35:65 to 80:20, in terms of the mass ratio of the polymer component (A) to the curable monomer (B).
[0167] In the curable resin composition, by setting the mass ratio of polymer component (A):curable monomer (B) within such a range, the flexibility of the obtained cured resin layer tends to be further improved and the solvent resistance of the cured resin layer tends to be maintained.
[0168] In addition, when the content of the curable monomer (B) in the curable resin composition is within the above range, for example, when a cured resin layer is obtained by a solution casting method, the solvent can be removed efficiently. Therefore, the problem of deformation such as curling and undulation caused by a prolonged drying process can be eliminated.
[0169] When a plurality of resins having different solvent solubilities are used in combination as the polymer component (A), such as a combination of the above-mentioned polyimide resin and a polyamide resin or a polyarylate resin, it is preferred to first dissolve the resins in solvents suitable for each, and then add a solution containing other resins to the low-boiling organic solvent containing the resins.
[0170] The curable resin composition may contain a polymerization initiator as desired. The polymerization initiator can be used without particular limitation as long as it can initiate a curing reaction, and examples thereof include a thermal polymerization initiator and a photopolymerization initiator.
[0171] Examples of the thermal polymerization initiator include organic peroxides and azo compounds.
[0172] Examples of the organic peroxide include dialkyl peroxides such as di-tert-butyl peroxide, tert-butyl isopropyl peroxide, and diisopropyl peroxide; diacyl peroxides such as acetyl peroxide, lauroyl peroxide, and benzoyl peroxide; ketone peroxides such as methyl ethyl ketone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; peroxyketals such as 1,1-bis(tert-butylperoxy)cyclohexane; tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, Hydroperoxides such as alkyl hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide; peroxyesters such as tert-butyl peroxyacetate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl carbonate; etc.
[0173] Examples of azo compounds include 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoyl azo)isobutyronitrile, and 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile.
[0174] Examples of the photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl]-2-methyl-propane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2 -dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone and other alkyl ketone photopolymerization initiators; 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, (2,4,6-trimethylbenzoyl)-phenylphosphine acid ethyl ester, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide and other phosphorus photopolymerization initiators; bis(η 5 -2,4-cyclopentadien-1-yl)-bis[2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl]titanium and other titanocene photopolymerization initiators; oxime ester photopolymerization initiators such as 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyl oxime)] and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime); benzophenone, p-chlorobenzophenone, benzoylbenzoic acid, methyl o-benzoylbenzoate, 4-methylbenzophenone, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4- Benzophenone-based photopolymerization initiators such as benzoyl-4'-methyl-diphenyl sulfide, 3,3'-dimethyl-4-methoxybenzophenone, 2,4,6-trimethylbenzophenone, and 4-(13-acryloyl-1,4,7,10,13-pentaoxatridecanyl)-benzophenone; thioxanthone-based photopolymerization initiators such as thioxanthone, 2-chlorothioxanthone, 3-methylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, and 4-isopropylthioxanthone; and the like.
[0175] Among the above-mentioned photopolymerization initiators, preferred are phosphorus-based photopolymerization initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, ethyl (2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide.
[0176] When the polymer component (A) is a thermoplastic resin having an aromatic ring, the polymer component (A) absorbs ultraviolet rays, resulting in difficulty in the curing reaction. However, by using the above-mentioned phosphorus-based photopolymerization initiator, the curing reaction can be efficiently carried out using light of a wavelength that is not absorbed by the above-mentioned polymer component (A).
[0177] The polymerization initiator may be used alone or in combination of two or more.
[0178] The content of the polymerization initiator is preferably 0.05 to 15% by mass, more preferably 0.05 to 10% by mass, and even more preferably 0.05 to 5% by mass, based on the total mass of the curable resin composition.
[0179] The curable resin composition may contain a photopolymerization initiating aid such as triisopropanolamine or 4,4'-diethylaminobenzophenone in addition to the polymer component (A), the curable monomer (B) and the polymerization initiator.
[0180] The solvent used in the preparation of the curable resin composition is not particularly limited, and examples thereof include: aliphatic hydrocarbon solvents such as n-hexane and n-heptane; aromatic hydrocarbon solvents such as toluene and xylene; halogenated hydrocarbon solvents such as dichloromethane, vinyl chloride, chloroform, carbon tetrachloride, 1,2-dichloroethane, and monochlorobenzene; alcohol solvents such as methanol, ethanol, propanol, butanol, and propylene glycol monomethyl ether; ketone solvents such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; ester solvents such as ethyl acetate and butyl acetate; cellosolve solvents such as ethyl cellosolve; ether solvents such as 1,3-dioxolane; and the like.
[0181] The content of the solvent in the curable resin composition is not particularly limited, but is usually 0.1 to 1000 g, preferably 1 to 100 g, based on 1 g of the polymer component (A). The viscosity of the curable resin composition can be adjusted to an appropriate viscosity by appropriately adjusting the amount of the solvent.
[0182] Furthermore, the curable resin composition may further contain known additives such as a plasticizer, an antioxidant, and an ultraviolet absorber within a range not impairing the object and effect of the present invention.
[0183] The method for curing the curable resin composition can be appropriately determined according to the types of the polymerization initiator and curable monomer used, and the details will be described in the section of the method for producing a laminate for a transparent conductive film described later.
[0184] [Properties of cured resin layer, etc.]
[0185] The thickness of the cured resin layer is 20 μm or less, preferably 15 μm or less, more preferably 12 μm or less, and further preferably 10 μm or less. The lower limit of the thickness of the cured resin layer is not particularly limited, but is usually 0.1 μm or more, preferably 0.2 μm or more.
[0186] When the thickness of the cured resin layer is 20 μm or less, a thin and lightweight laminate for forming a transparent conductive film can be easily obtained, and a laminate for forming a transparent conductive film having excellent handleability can be obtained.
[0187] In addition, since the cured resin layer is thin, a transparent conductive film with high transparency, thinness, and lightness can be obtained. Therefore, in applications such as organic EL displays that require thinness, the transparent conductive film does not cause an increase in the overall thickness of the applicable device, and is therefore preferred. In addition, in the case of a thin transparent conductive film, the flexibility and bending resistance of the transparent conductive film after installation can be improved.
[0188] As described above, the cured resin layer of the transparent conductive film forming laminate according to the embodiment of the present invention has an absolute value of thermal deformation rate of 1.2% or less when heated to 150° C. Therefore, the laminate has excellent heat resistance and can obtain a transparent conductive film forming laminate having excellent heat resistance.
[0189] In particular, since the cured resin layer has high heat resistance, even if a laminate for forming a transparent conductive film is produced by a process accompanied by heating after the formation of the cured resin layer, such as forming a conductive material layer on the cured resin layer by sputtering, evaporation, coating, etc. and further heating the conductive material layer to form a transparent conductive layer, problems are not likely to occur. Specifically, it is possible to avoid a situation where the transparent conductive layer cannot be well formed or the transparent conductive layer cannot exert sufficient electrical properties due to deformation of the cured resin layer. From the same point of view, the absolute value of the thermal deformation rate of the cured resin layer caused by heating to 150°C is preferably 0.8% or less.
[0190] The thermal deformation rate of the cured resin layer is a characteristic value measured by the method described in the examples described later. In the examples, the thickness of the cured resin layer is adjusted to 20 μm for measurement, but the cured resin layer is thin, and in order to avoid the problem of elongation of the cured resin layer when set in the fixture of the thermomechanical analysis device, the thickness of the cured resin layer is stacked to be more than 20 μm for measurement.
[0191] As described later, from the viewpoint that a cured resin layer can be easily formed by curing the coating film obtained by applying the curable resin composition on the process film, the cured resin layer is preferably a cured product of the coating film of the curable resin composition formed on the surface (second surface) of the process film where no peeling layer is provided.
[0192] The above-mentioned cured resin layer also has excellent solvent resistance. From the viewpoint of excellent solvent resistance, for example, even when an organic solvent is used when forming other layers on the surface of the cured resin layer, the surface of the cured resin layer is basically insoluble. Therefore, for example, when a transparent conductive layer is formed on the surface of the cured resin layer by a coating method using a resin solution containing an organic solvent, the components of the cured resin layer are not easily mixed into the transparent conductive layer, and the electrical properties of the transparent conductive layer are not easily reduced.
[0193] From this point of view, the gel fraction of the cured resin layer is preferably 90% or more, more preferably 94% or more. The cured resin layer having a gel fraction of 90% or more has excellent solvent resistance, so even if an organic solvent is used when forming another layer on the surface of the cured resin layer by coating, the surface of the cured resin layer is hardly dissolved, and a laminate for a transparent conductive film having excellent solvent resistance can be easily obtained.
[0194] Here, the gel fraction is obtained in the following manner: a cured resin layer cut into 100 mm × 100 mm is wrapped with a 150 mm × 150 mm nylon mesh (#120) of pre-measured mass, immersed in toluene (100 mL) for 3 days, taken out and dried at 120°C for 1 hour, then placed at 23°C and 50% relative humidity for 3 hours for humidity adjustment, and then its mass is measured and obtained by the following formula.
[0195] Gel fraction (%) = [(mass of residual resin after immersion) / (mass of resin before immersion)] × 100
[0196] The interlayer adhesion between the cured resin layer and the transparent conductive layer is excellent. That is, the transparent conductive layer can be formed without providing an anchor coating layer on the cured resin layer.
[0197] The cured resin layer is preferably colorless and transparent. When the cured resin layer is colorless and transparent, the laminate for forming a transparent conductive film according to the embodiment of the present invention can be preferably used for optical applications.
[0198] The cured resin layer has a low birefringence and excellent optical isotropy. The in-plane phase difference of the cured resin layer is usually 20 nm or less, preferably 15 nm or less. The phase difference in the thickness direction is usually -500 nm or less, preferably -450 nm or less. In addition, the value (birefringence) obtained by dividing the in-plane phase difference by the thickness of the cured resin layer is usually 100×10 -5 Below, preferably 20×10 -5 the following.
[0199] When the in-plane phase difference, thickness direction phase difference and birefringence of the curable resin layer are within the above-mentioned ranges, a laminate for forming a transparent conductive film having low birefringence and excellent optical isotropy can be obtained, and the transparent conductive film prepared using the laminate for forming a transparent conductive film can be preferably used for optical purposes.
[0200] The elongation at break of the cured resin layer is preferably 2.5% or more, more preferably 2.6% or more, and further preferably 2.7% or more. When the elongation at break of the cured resin layer is 2.5% or more, it is easy to adjust the elongation at break of the laminate for forming a transparent conductive film to about 2% or more, and as a result, it is easy to obtain a laminate for forming a transparent conductive film with excellent flexibility.
[0201] 1-2. Process film
[0202] The process film has a function of protecting the cured resin layer and other layers arbitrarily provided below when the transparent conductive film-forming laminate or the transparent conductive film described below is stored or transported, and is a film to be peeled off in a given process.
[0203] The process film has, for example, a substrate layer. The process film may be provided with other layers other than the substrate layer. When a release layer is provided on one surface (first surface) of the process film, the above-mentioned cured resin layer is provided on the surface (second surface) of the process film opposite to the side provided with the release layer. Figure 1 (a) and Figure 1 In (b), the first surface of the process film 1 or 1A is indicated by the symbol S1, and the second surface of the process film 1 or 1A is indicated by the symbol S2.
[0204] By providing the laminate for transparent conductive film with a process film, a laminate for transparent conductive film formation that protects the cured resin layer and has high handleability can be obtained. In addition, when a curable resin composition is applied to the process film, when a peeling layer is provided on the surface of the process film, the coating film sometimes becomes uneven. In the manufacturing process of the laminate for transparent conductive film according to an embodiment of the present invention, a uniform coating film can be obtained by applying the curable resin composition to the second surface of the process film where the peeling layer is not provided. The laminate for transparent conductive film formation can be as follows Figure 1 As shown in (a), a process film may be provided on one side of the cured resin layer. Figure 1As shown in (b), there are process films on both sides of the cured resin layer. In the latter case, it is preferred to use two process films, and make the process film that is peeled off first a film that is easier to peel off. In this case, as long as at least one of the process films 1A and 1B has a second surface without a peeling layer and a cured resin layer is formed on its surface. In the case of applying a curable resin composition on the process film in order to form a cured resin layer, it is preferred to form a coating of the curable resin composition on the second surface of the process film having the second surface in the process films 1A and 1B so as to obtain a uniform coating.
[0205] The process film is preferably in the form of a sheet or a film. The sheet or film is not limited to a long strip, but also includes a short flat plate.
[0206] Examples of the substrate layer of the process film include: paper substrates such as glassine paper, coated paper, and fully pulped paper; laminated paper obtained by laminating thermoplastic resins such as polyethylene and polypropylene on these paper substrates; materials obtained by filling the above-mentioned paper substrates with cellulose, starch, polyvinyl alcohol, acrylic-styrene resins, etc.; or plastic films such as polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, and polyolefin films such as polyethylene and polypropylene; glass, etc.
[0207] The process film may have a release layer. In this case, the process film has the release layer only on one surface (the first surface).
[0208] The release layer can be formed using a conventionally known release agent such as a silicone-based release agent, a fluorine-based release agent, an alkyd-based release agent, or an olefin-based release agent.
[0209] The thickness of the release layer is not particularly limited, but is usually 0.02 to 2.0 μm, more preferably 0.05 to 1.5 μm.
[0210] From the viewpoint of ease of handling, the thickness of the process film is preferably 1 to 500 μm, more preferably 5 to 300 μm.
[0211] 1-3. Other layers
[0212] The process film may have a layer other than the release layer, such as an easy-adhesion layer and an antistatic layer, but preferably, no layer other than the release layer is provided on the second surface on which the release layer is not provided.
[0213] Among the constituent layers of the laminate for transparent conductive film, the portion (separation layer) peeled off from the process film in a given process includes a cured resin layer. The cured resin layer is laminated on the process film without sandwiching other layers, so the cured resin layer is located on one of the outermost surfaces of the separation layer. On the other surface side of the separation layer, an easy-adhesive layer, an antistatic layer, etc. other than the cured resin layer may also be provided, but since the separation layer is a layer constituting the transparent conductive film after the process film is removed, it is preferably thin, and the number and thickness of layers other than the cured resin layer are preferably set to a minimum.
[0214] 2. Transparent conductive film
[0215] The transparent conductive film of the embodiment of the present invention sequentially comprises a process film, a cured resin layer and a transparent conductive layer. When the transparent conductive film is actually used, the process film is peeled off from the transparent conductive film, and is loaded into a display, a solar cell panel, or attached to a substrate of a touch sensor for a touch panel for use. As for the method of applying the transparent conductive film to the applied part, for example, when the transparent conductive film has an adhesive layer as described later, it can be attached to the applied part through the adhesive layer, and the process film is peeled off and removed after the attachment.
[0216] The specific configuration of the transparent conductive film according to the embodiment of the present invention is shown in Figure 2 .
[0217] Figure 2 The transparent conductive film 20 shown in (a) has a transparent conductive layer 3 on one side of a cured resin layer 2 and a process film 1 on the side of the cured resin layer 2 opposite to the transparent conductive layer 3 .
[0218] The transparent conductive layer 3 is formed, for example, so as to cover the entire surface of the cured resin layer 2. In addition, the transparent conductive layer 3 can be patterned into a desired shape by an appropriate method such as etching. Figure 2 The transparent conductive film 21 shown in (b) has a patterned transparent conductive layer 31 on one side of the cured resin layer 2. It should be noted that by selectively disposing a transparent conductive material on the cured resin layer 2, a transparent conductive layer 31 having a desired pattern shape can be formed on the cured resin layer 2 without going through a process such as etching.
[0219] If from the Figure 2 The transparent conductive film in the state shown has poor workability if the process film 1 is peeled off and removed. Therefore, it is preferable to peel off and remove the process film 1 after applying the transparent conductive film to the application portion such as an adherend.
[0220] The thickness of the transparent conductive film can be appropriately determined according to the intended use, etc. From the viewpoint of workability, the substantial thickness of the transparent conductive film according to the embodiment of the present invention is preferably 0.3 to 50 μm, more preferably 0.5 to 25 μm, and even more preferably 0.7 to 12 μm.
[0221] It should be noted that the “substantial thickness” refers to the thickness in the state of use. That is, although the transparent conductive film has a process film, the thickness of the portion (process film, etc.) removed during use is not included in the “substantial thickness”.
[0222] In this specification, the term "transparent" in a transparent conductive film means that the light transmittance at a wavelength of 450 nm is 80% or more.
[0223] The transparent conductive film according to the embodiment of the present invention has a low birefringence and excellent optical isotropy.
[0224] The in-plane phase difference of the transparent conductive film is usually 20 nm or less, preferably 15 nm or less. The phase difference in the thickness direction is usually -500 nm or less, preferably -450 nm or less. In addition, the value (birefringence) obtained by dividing the in-plane phase difference by the thickness of the transparent conductive film is usually 100×10 -5 Below, preferably 20×10 -5 the following.
[0225] When the in-plane retardation, thickness direction retardation, and birefringence of the transparent conductive film are within the above ranges, the transparent conductive film according to the embodiment of the present invention has excellent optical isotropy and can be preferably used for optical applications.
[0226] As the conductive material constituting the transparent conductive layer, metals, alloys, metal oxides, conductive compounds, and mixtures thereof can be listed. Specifically, antimony-doped tin oxide (ATO); fluorine-doped tin oxide (FTO); semi-conductive metal oxides such as tin oxide, germanium-doped zinc oxide (GZO), zinc oxide, indium oxide, indium tin oxide (ITO), and zinc indium oxide (IZO); metals such as gold, silver, chromium, and nickel; mixtures of these metals and conductive metal oxides; inorganic conductive substances such as copper iodide and copper sulfide; organic conductive materials such as polyaniline, polythiophene, and polypyrrole; and the like. Metals such as silver can constitute a transparent conductive layer by aggregating metals in a particle state such as nanofillers, nanorods, and nanofibers.
[0227] The method for forming the transparent conductive layer is not particularly limited. Examples thereof include vapor deposition, sputtering, ion plating, thermal CVD, plasma CVD, etc. In addition, for example, a coating material containing a particulate metal can be applied to the transparent conductive film laminate to obtain a transparent conductive layer from a coating film.
[0228] The thickness of the transparent conductive layer can be appropriately selected depending on the intended use, etc. It is usually 10 nm to 50 μm, and preferably 20 nm to 20 μm.
[0229] The transparent conductive film of the embodiment of the present invention is not limited to Figure 2 The film having the structure shown above may further contain one or two or more other layers within the range not impairing the object of the present invention.
[0230] Examples of the other layers include a shock absorbing layer, an adhesive layer, etc. The arrangement positions of the other layers are not particularly limited.
[0231] The impact absorbing layer is a layer that protects the transparent conductive layer when an impact is applied to the transparent conductive layer. The raw material for forming the impact absorbing layer is not particularly limited, and examples thereof include acrylic resins, urethane resins, silicone resins, olefin resins, and rubber materials.
[0232] The method for forming the impact absorbing layer is not particularly limited, and for example, a method of applying a solution for forming the impact absorbing layer, which contains a raw material for forming the impact absorbing layer and other components such as a solvent as required, on a layer to be laminated, drying the resulting coating film, and heating as required can be cited.
[0233] Alternatively, the impact absorbing layer may be separately formed on a release substrate, and the resulting film may be transferred onto a layer to be laminated.
[0234] The thickness of the impact absorbing layer is usually 1 to 100 μm, preferably 5 to 50 μm.
[0235] The adhesive layer is a layer used when the transparent conductive film is pasted to the adherend. The material forming the adhesive layer is not particularly limited, and known adhesives or adhesives, heat-sealing materials, etc. such as acrylic, silicone, and rubber can also be used. For the transparent conductive film, when the adhesive layer is formed on the opposite side of the surface of the cured resin layer relative to the process film, the process film can be peeled off after the transparent conductive film is pasted to the adherend using the adhesive layer, so as to easily form a thin film having a cured resin layer and a transparent conductive layer on the adherend. In the present invention, since the process film is soft, such pasting can be easily performed, and the process film can also be easily peeled off. The transparent conductive film can have a peeling film for protecting the adhesive layer on the opposite side of the adhesive layer relative to the cured resin layer. Thus, the transparent conductive film has a process film and a peeling film on the outermost layer on both sides, which is easy to handle.
[0236] 3. Method for manufacturing a laminate for forming a transparent conductive film
[0237] The laminate for forming a transparent conductive film according to the embodiment of the present invention is produced using a process film. By using the process film, the laminate for forming a transparent conductive film can be produced efficiently and easily. The method having the following steps 1 and 2 is particularly preferred.
[0238] Step 1: Step of forming a curable resin layer on a process film using a curable resin composition containing a polymer component (A) and a curable monomer (B)
[0239] Step 2: Step of curing the curable resin layer obtained in step 1 to form a cured resin layer
[0240] Figure 3 An example of a process for producing a laminate for a transparent conductive film according to an embodiment of the present invention is shown. Figure 3 (a) shows the state before forming the curable resin layer, Figure 3 (b) corresponds to the above step 1, and in addition, Figure 3 (c) corresponds to the above step 2. Figure 3 (a)~ Figure 3 (c) Figure 1 (a) Similarly, the first surface of the process film 1 is denoted by the symbol S1, and the second surface of the process film 1 is denoted by the symbol S2.
[0241] (Process 1)
[0242] First, a curable resin composition containing a polymer component (A) and a curable monomer (B) is used to coat a process film ( Figure 3 The surface (second surface) of the symbol 1) of (a) is formed with a curable resin layer ( Figure 3 (b) Symbol 2a) The method for forming the curable resin layer is preferably a coating method.
[0243] The method of applying the curable resin composition to the process film is not particularly limited, and can utilize known coating methods such as spin coating, spray coating, rod coating, knife coating, roll coating, blade coating, die coating, gravure coating, etc. By applying the curable resin composition to the second surface of the process film, a uniform coating film can be easily obtained.
[0244] The method of drying the obtained coating film is not particularly limited, and existing known drying methods such as hot air drying, hot roller drying, infrared irradiation, etc. can be used. When the polymer component (A) is dissolved in a solvent alone to form a resin layer without using a curable monomer (B), it is easy to cause the surface of the resin layer to dry first and the solvent to remain inside the resin layer (the so-called "skinning"). As described above, the thermal deformation rate of the cured resin layer of the embodiment of the present invention is small, and the Tg of the polymer component (A) contained in the curable resin composition used to form the cured resin layer is usually very high. In this case, the above-mentioned skinning phenomenon is particularly prone to occur. However, by making the above-mentioned curable resin composition contain a curable monomer (B), when the coating film obtained by using a solution casting method is dried, the fluidity of the resin composition is maintained, and the solvent can be efficiently removed to the inside of the resin layer.
[0245] The drying temperature of the coating film is usually 30 to 150°C, preferably 50 to 100°C.
[0246] The thickness of the dried coating film (curable resin layer) is not particularly limited, and since there is basically no difference in thickness after curing, it may be the same as the thickness of the curable resin layer described above.
[0247] (Process 2)
[0248] Next, the curable resin layer obtained in step 1 is cured to form a cured resin layer. The cured resin layer becomes a cured resin layer ( Figure 3 (c) symbol 2).
[0249] The method for curing the curable resin layer is not particularly limited, and a known method can be used. For example, when the curable resin layer is a layer formed using a curable resin composition containing a thermal polymerization initiator, the curable resin layer can be cured by heating the curable resin layer. The heating temperature is usually 30 to 150° C., preferably 50 to 100° C.
[0250] In addition, when the curable resin layer is formed using a curable resin composition containing a photopolymerization initiator, the curable resin layer can be cured by irradiating the curable resin layer with active energy rays. The active energy rays can be irradiated using a high pressure mercury lamp, an electrodeless lamp, a xenon lamp, or the like.
[0251] The wavelength of the active energy ray is preferably 200 to 400 nm, more preferably 350 to 400 nm. The irradiation amount is usually 50 to 1000 mW / cm 2 , light intensity 50~5000mJ / cm 2 , preferably 1000 to 5000 mJ / cm 2The irradiation time is usually 0.1 to 1000 seconds, preferably 1 to 500 seconds, and more preferably 10 to 100 seconds. Considering the heat load of the light irradiation step, multiple irradiations may be performed to meet the above light amount.
[0252] In this case, in order to prevent degradation of the polymer component (A) and coloration of the cured resin layer caused by irradiation with active energy rays, the curable resin composition may be irradiated with active energy rays through an optical filter that absorbs light of wavelengths not necessary for the curing reaction. According to this method, light of wavelengths not necessary for the curing reaction and causing degradation of the polymer component (A) is absorbed by the optical filter, so degradation of the polymer component (A) is suppressed, and a colorless and transparent cured resin layer is easily obtained.
[0253] As the optical filter, a resin film such as a polyethylene terephthalate film can be used. When a resin film is used, it is preferred to provide a step of laminating the resin film such as a polyethylene terephthalate film on the curable resin layer between step 1 and step 2. It should be noted that the resin film is usually peeled off after step 2.
[0254] In addition, the curable resin layer can also be cured by irradiating the curable resin layer with an electron beam. In the case of irradiating an electron beam, the curable resin layer can usually be cured without using a photopolymerization initiator. In the case of irradiating an electron beam, an electron beam accelerator or the like can be used. The irradiation amount is usually in the range of 10 to 1000 krad. The irradiation time is usually 0.1 to 1000 seconds, preferably 1 to 500 seconds, and more preferably 10 to 100 seconds.
[0255] The curing of the curable resin layer can be performed in an inert gas atmosphere such as nitrogen as needed. By performing the curing in an inert gas atmosphere, it is easy to avoid the effects of oxygen, moisture, etc. on the curing.
[0256] 4. Method for manufacturing transparent conductive film
[0257] The method for producing the transparent conductive film according to the embodiment of the present invention is preferably a method including the following steps 3 and 4.
[0258] Step 3: Step of forming a conductive material layer on the cured resin layer of the laminate for a transparent conductive film
[0259] Step 4: A step of heating the conductive material layer obtained in step 3 to 140° C. or higher to form a transparent conductive layer
[0260] The method for producing the transparent conductive film according to the embodiment of the present invention may be a method including the following step 5.
[0261] Step 5: A step of patterning the transparent conductive layer obtained in step 4 into a predetermined shape
[0262] Figure 4 An example of a process for producing a transparent conductive film according to an embodiment of the present invention is shown in FIG. Figure 4 (a) shows a laminate for a transparent conductive film before a conductive material is arranged. Figure 4 (b) corresponds to the above step 3, Figure 4 (c) corresponds to the above step 4, Figure 4 (d) corresponds to the above step 5.
[0263] (Process 3)
[0264] A conductive material layer ( Figure 4 (b) Symbol 3a).
[0265] As a method for providing the conductive material layer, PVD methods such as sputtering, EB evaporation, and ion plating, and CVD methods can be used. Alternatively, a method of forming the conductive material layer by applying a composition containing a conductive material and a solution on a curing resin layer and drying the composition can be used.
[0266] The conductive material layer is formed, for example, so as to cover the entire surface of the cured resin layer.
[0267] (Process 4)
[0268] In step 4, the conductive material layer formed in step 3 is heated to 140° C. or higher to crystallize the conductive material, thereby forming a transparent conductive layer ( Figure 4 (c) Symbol 3). Thus, the transparent conductive film 20 can be obtained.
[0269] As a method of heating the conductive material layer, heating with an electric furnace or the like can be adopted.
[0270] The transparent conductive layer can be formed by various methods, but heating is required to crystallize the conductive material layer. In addition, when the conductive material layer is formed by coating, it is necessary to heat and dry after coating the composition containing the conductive material. As described above, the absolute value of the thermal deformation rate caused by heating to 150° C. of the cured resin layer of the embodiment of the present invention is less than 1.2%, and therefore, it is not easily affected by heating when forming the transparent conductive layer.
[0271] By continuously forming a conductive material layer on the cured resin layer and performing a heat treatment while conveying the long process film on which the cured resin layer is formed in a certain direction, a long laminate having a transparent conductive layer formed on the cured resin layer can be efficiently manufactured.
[0272] (Process 5)
[0273] In step 5, a portion of the transparent conductive layer formed in step 4 is removed to form a transparent conductive layer ( Figure 4 (d) Symbol 31). By going through step 5, a transparent conductive film 21 having a patterned transparent conductive layer can be obtained.
[0274] As a method of patterning the transparent conductive layer, for example, a method of partially removing the transparent conductive layer by bringing an etching solution into contact with the transparent conductive layer after masking a portion corresponding to a desired shape, or a method of removing unnecessary portions by irradiating laser light can be adopted.
[0275] It should be noted that by selectively disposing a transparent conductive material on a cured resin layer and heating the material to form a transparent conductive layer, a transparent conductive layer having a desired pattern shape can be formed on the cured resin layer without performing a process such as etching.
[0276] After obtaining the transparent conductive film through the above steps, an adhesive layer may be provided on the transparent conductive layer. As is clear from the above description, the transparent conductive film obtained by the above production method is thin, has excellent heat resistance, excellent transparency and optical isotropy, and the transparent conductive layer has good electrical properties.
[0277] Example
[0278] Next, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples at all.
[0279] The physical property values of the cured resin layer and the laminate for a transparent conductive film in each of the Examples and Comparative Examples were measured and evaluated according to the following procedures.
[0280] <Measurement of thermal deformation rate of cured resin layer>
[0281] The cured resin layer corresponding to the first polyethylene terephthalate (PET) film on the cured resin layer side of the process film was peeled off and stacked into 4 sheets to form a laminate with a thickness of 20 μm. Then, it was cut into test pieces of 5 mm × 30 mm, and a thermomechanical analyzer (TMA4000SE manufactured by NETZSCH Japan Co., Ltd.) was used, and the distance between the chucks was set to 20 mm to clamp the laminate of the above-mentioned cured resin layer. Then, the laminate of the above-mentioned cured resin layer was heated from 25°C to 150°C at 5°C / min, and then cooled to 25°C at 5°C / min. Then, the rate of change of the displacement in the longitudinal direction before and after heating (the value of the ratio of the displacement amount to the distance between the chucks of 20 mm expressed as a percentage) was taken as the thermal deformation rate of the cured resin layer. It should be noted that the case where the laminate of the cured resin layer has shrunk is set to a negative value, and the case where the elongation has occurred is set to a positive value.
[0282] <Elongation at break of cured resin layer>
[0283] The cured resin layer was cut into a test piece of 15 mm × 150 mm, and the elongation at break was measured according to JIS K7127: 1999. Specifically, the distance between the chucks was set to 100 mm, and the test piece was placed in a tensile testing machine (Autograph, Shimadzu Corporation) and a tensile test was performed at a speed of 200 mm / min, thereby measuring the elongation at break [%]. It should be noted that when the test piece does not have a yield point, the tensile fracture strain is used as the elongation at break, and when it has a yield point, the strain at the yield point is used as the elongation at break.
[0284] <Removability of process film in laminate for transparent conductive film>
[0285] After peeling off the second process film of the transparent conductive film laminate (width 50 mm), the first process film (Examples 1, 2, Comparative Examples 1 to 3 are the first PET film, and Comparative Example 4 is the biaxially stretched polyester film) was peeled off at a peeling angle of 180° and a peeling speed of 0.3 m / min using TENSILON universal testing machine RTG-1225 (A&D Company) in accordance with JIS Z0237:2000, and the appearance change of the transparent conductive film laminate after the test was evaluated. It should be noted that the above-mentioned peeling test is performed by bonding the surface of the cured resin layer exposed by peeling off the second process film to a glass plate using a double-sided adhesive film, and then peeling off the first process film. The case where there is no shape change of the cured resin layer is evaluated as qualified ("A"), and the case where a shape change occurs is evaluated as unqualified ("B").
[0286] [Example 1]
[0287] The curable resin composition 1 for forming a cured resin layer was prepared according to the following procedure.
[0288] As a polymer component, 100 parts by mass of pellets of polyimide resin (PI) (manufactured by Kawamura Industry Co., Ltd., product name KPI-MX300F, Tg=354°C, weight average molecular weight 280,000) were dissolved in methyl ethyl ketone (MEK) to prepare a 15% by mass solution of PI. Next, 122 parts by mass of tricyclodecane dimethanol diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., A-DCP) as a curable monomer and 5 parts by mass of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (manufactured by BASF, Irgacure819) as a polymerization initiator were added to the solution and mixed to prepare a curable resin composition 1. It should be noted that the curable monomers and polymerization initiators used in this embodiment and other experimental examples are raw materials containing no solvent and having a total solid content of 100%.
[0289] Next, a first PET film (manufactured by Toyobo Co., Ltd., Cosmoshine PET100A-4160, thickness 100 μm) having an easy-adhesion layer on one side was used as a first step film, and a curable resin composition was applied to the side of the PET film opposite to the easy-adhesion layer. The coated film was heated at 90° C. for 3 minutes and dried.
[0290] Furthermore, a second PET film (manufactured by Toyobo Co., Ltd., Cosmoshine PET50A-4160, thickness 50 μm) having an easy-adhesive layer on one side as a second step film was laminated on the dried coating film in a manner relative to the side opposite to the easy-adhesive surface. Then, a conveyor-type ultraviolet irradiation device (manufactured by Eye Graphics, product name: ECS-401GX) was used to irradiate the film using a high-pressure mercury lamp (manufactured by Eye Graphics, product name: H04-L41) at an ultraviolet lamp height of 100 mm, an ultraviolet lamp output of 3 kW, and a light wavelength of 365 nm with an illumination of 400 mW / cm 2 , light intensity is 800mJ / cm 2 The curing reaction was carried out by ultraviolet irradiation with the second PET film interposed therebetween under the conditions of 100 μm (manufactured by Orc Manufacturing, measured by ultraviolet photometer UV-351) to form a cured resin layer with a thickness of 5 μm, thereby obtaining a laminate for a transparent conductive film.
[0291] [Example 2]
[0292] A laminate for a transparent conductive film was obtained in the same manner as in Example 1 except that the curable monomer was changed to a combination of the above-mentioned tricyclodecane dimethanol diacrylate and a cyclopolymerizable monomer (FX-AO-MA manufactured by Nippon Shokubai Co., Ltd.) (mixing ratio 1:1).
[0293] [Example 3]
[0294] A laminate for a transparent conductive film was obtained in the same manner as in Example 1 except that the total amount of the curable monomer was made into the same cyclopolymerizable monomer as used in Example 2.
[0295] [Comparative Example 1]
[0296] A laminate for a transparent conductive film was produced in the same manner as in Example 1 except that pellets of a polysulfone resin (PSF) (ULTRASON S6010 manufactured by BASF, Tg=187° C.) were used instead of pellets of a polyimide resin (PI) as a polymer component.
[0297] [Comparative Example 2]
[0298] A methyl ethyl ketone solution of a polyimide resin was prepared by the same procedure as in Example 1 except that no curable monomer and polymerization initiator were added, thereby obtaining a resin composition 2. Then, using the resin composition 2, only a resin layer was formed instead of curing the resin layer by the same procedure as in Example 1 except that no ultraviolet irradiation was performed, thereby obtaining a laminate for a transparent conductive film.
[0299] Table 1 shows the measurement results of each example and comparative example.
[0300] [Table 1]
[0301] Table 1
[0302]
[0303] ※ Meaning of symbols in Table 1
[0304] PI: Polyimide resin
[0305] PSF: Polysulfone resin
[0306] DCP: Tricyclodecane dimethanol diacrylate
[0307] AE: Cyclic polymerization monomer
[0308] It is clear from Table 1 that in Examples 1 to 3, a cured resin layer using a curable monomer is prepared by containing a polymer component with high heat resistance, and a process film without a peeling layer is used, thereby achieving the problem of peeling off the process film (first PET film) from the cured resin layer with a thickness of less than 10 μm.
[0309] In Comparative Example 1, although the process film (first PET film) could be peeled off from the cured resin layer having a thickness of 10 μm or less without any problem, the cured resin layer had a large thermal deformation rate and was not suitable for the transparent conductive layer forming step.
[0310] In Comparative Example 2, since no curable monomer was contained, the second step film could not be peeled off, and the evaluation of peelability could not be performed.
Claims
1. A transparent conductive film laminate, which is a transparent conductive film laminate for forming a transparent conductive film, wherein: The transparent conductive film laminate comprises a process film and a cured resin layer in this order. The cured resin layer is a layer formed of a cured product of a curable resin composition, wherein the curable resin composition contains a polymer component (A) and a curable monomer (B). The polymer component (A) is a polyimide resin, The absolute value of the thermal deformation rate of the cured resin layer caused by heating to 150° C. is 1.2% or less, The thickness of the cured resin layer is less than 20 μm, The process film has a first surface optionally provided with a release layer and a second surface not provided with a release layer, The cured resin layer is formed on the second surface of the process film.
2. The laminate for a transparent conductive film according to claim 1, wherein The glass transition temperature of the polymer component (A) is 250° C. or higher.
3. The laminate for a transparent conductive film according to claim 1 or 2, wherein: The weight average molecular weight of the polymer component (A) is 100,000 or more.
4. The laminate for a transparent conductive film according to claim 1 or 2, wherein: The polyimide resin is soluble in methyl ethyl ketone.
5. The laminate for a transparent conductive film according to claim 1 or 2, wherein: The polyimide resin has a fluorine group in the molecule.
6. The laminate for a transparent conductive film according to claim 1 or 2, wherein: The elongation at break of the cured resin layer is greater than 2.5%.
7. A transparent conductive film, comprising: The laminate for a transparent conductive film according to any one of claims 1 to 6, and A transparent conductive layer is provided on the cured resin layer of the laminate for a transparent conductive film.
8. A method for manufacturing a transparent conductive film, the method comprising: A step of forming a conductive material layer on the cured resin layer of the laminate for a transparent conductive film according to any one of claims 1 to 6, and The conductive material layer is heated to 140° C. or higher to form a transparent conductive layer.
